STUDI PEMANFAATAN LIMBAH AIR CUCIAN BERAS TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABE MERAH (Capsicum annuum L.) - Gae Lada, Yulius; Kotouki, Nikson (Universitas Islam Malang, 2024)
Rice washing water waste is a natural growth regulator that contains the hormones auxin, gibberellins and cytokinins, is easy to obtain and has a function in encouraging plant growth and development. This research aims to determine the effect of rice washing water waste on the growth and production of red chili plants (Capsicum annuum L.). The research method used in this study was an experimental method using a completely randomized design (CRD) with 6 treatments which were repeated 5 times, so that 30 (thirty) experimental units were obtained with concentrations: control 0 ml/l (A0), 50 ml/ 1 liter of water (A1), 70 ml/1 liter of water (A2), 90 ml/1 liter of water (A3), 110 ml/1 liter of water (A4) and 130 ml/1 liter of water (A5). The parameters observed were plant height (cm); number of leaves (strands); leaf width (cm); leaf length (cm) and number of fruits. From the research results, it was found that the provision of rice washing water on the growth and yield of red chili plants (Capsicum annum L.) generally had a significantly different effect on the growth and yield of red chili plants. On leaf length parameters, the provision of rice washing water did not have a significantly different effect. The best treatment was obtained at a concentration of 130 ml/liter which provided optimal results for each parameter.